Acute toxicity of bayluscide on milkfish juveniles in different salt concentrations. - Velasco, John Mark (1999.)
The toxic effects of Bayluscide 250EC at concentrations of 0.25, 0.5, 1.0, and 2.0 ppm was tested on milkfish juveniles with an average weight of 0.2 g. The effect of salinity on the toxicity of Bayluscide was also tested using 25 and 32 ppt salt concentrations. Thirty tanks were used, each filled with 30 liters of water. Ten milkfish juveniles were stocked in each tank. Fish mortalities and temperature were recorded every hour for the first eight hours, at the 24th, 48th, 72nd and 96th hour. DO levels were maintained at an optimum range using aeration. pH was taken at the beginning and at the end of the experiment. The 24-hour LC50 for the 25 ppt salt concetration was recorded at 1.19 ppm while the 24-hour LC50 for the 32 ppt was recorded to be at 0.72 ppm. The effect of salinity on the toxicity of Bayluscide to milkfish juveniles was found to be significant with the higher salt concentration of 32 ppt resulting to higher mortalities. A slight increase in pH was recorded at the two different salinities. One-hundred percent mortality was recorded within 24 hours at a Bayluscide concentration of 2ppm for both salt concentrations.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Milkfish -- Salt Concentration; Bayluscide -- Toxic